2019
DOI: 10.1002/anie.201902578
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Salts Induce Thermally Reversible and Anti‐Freezing Cellulose Hydrogels

Abstract: Inspired by the anti‐freezing mechanisms found in nature, ionic compounds (ZnCl2/CaCl2) are integrated into cellulose hydrogel networks to enhance the freezing resistance. In this work, cotton cellulose is dissolved by a specially designed ZnCl2/CaCl2 system, which endows the cellulose hydrogels specific properties such as excellent freeze‐tolerance, good ion conductivity, and superior thermal reversibility. Interestingly, the rate of cellulose coagulation could be promoted by the addition of extra water or gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
247
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 400 publications
(247 citation statements)
references
References 24 publications
0
247
0
Order By: Relevance
“…Compared to conventional isotropic organohydrogel systems, the structured ELP‐surfactant organofibers show extraordinary mechanical performance. For example, synthesized polymer gel networks have limited tensile strength at the scale of kiloPascal level, [28–31] and show tenuous modulus property [32–35] . In our system, the strength of anisotropic ELP‐surfactant organofibers is at least one order of magnitude higher than the isotropic counterparts aforementioned, highlighting their robustness in term of mechanical properties (Table 1).…”
Section: Gel/fibers Solvent Tensilestrength [Mpa] Young's Modulus [Mpmentioning
confidence: 71%
“…Compared to conventional isotropic organohydrogel systems, the structured ELP‐surfactant organofibers show extraordinary mechanical performance. For example, synthesized polymer gel networks have limited tensile strength at the scale of kiloPascal level, [28–31] and show tenuous modulus property [32–35] . In our system, the strength of anisotropic ELP‐surfactant organofibers is at least one order of magnitude higher than the isotropic counterparts aforementioned, highlighting their robustness in term of mechanical properties (Table 1).…”
Section: Gel/fibers Solvent Tensilestrength [Mpa] Young's Modulus [Mpmentioning
confidence: 71%
“…Compared to conventional isotropic organohydrogel systems, the structured ELP‐surfactant organofibers show extraordinary mechanical performance. For example, synthesized polymer gel networks have limited tensile strength at the scale of kiloPascal level, [28–31] and show tenuous modulus property [32–35] . In our system, the strength of anisotropic ELP‐surfactant organofibers is at least one order of magnitude higher than the isotropic counterparts aforementioned, highlighting their robustness in term of mechanical properties (Table 1).…”
Section: Gel/fibers Solvent Tensilestrength [Mpa] Young's Modulus [Mpmentioning
confidence: 71%
“…It is observed that the hydrogel microfiber maintains good elasticity at −40 °C with almost coincident tensile curve to that at 25 °C, and the fiber becomes brittle lower than −50 °C. The frost resistance of hydrogel microfiber is attributed to the presence of glycerol, which is known to significantly inhibit ice crystallization in hydrogel systems 32,33…”
Section: Resultsmentioning
confidence: 99%